Prime Field ECDSA Signature Processing for Reconfigurable Embedded Systems - Benjamin Glas; Oliver Sander; Vitali Stuckert; Klaus D. Müller-Glaser; Jürgen Becker (International Journal of Reconfigurable Computing)
Growing ubiquity and safety relevance of embedded systems strengthen the need to protect their functionality against malicious attacks. Communication and system authentication by digital signature schemes is a major issue in securing such systems. This contribution presents a complete ECDSA signature processing system over prime fields for bit lengths of up to 256 on reconfigurable hardware. By using dedicated hardware implementation, the performance can be improved by up to two orders of magnitude compared to microcontroller implementations. The flexible system is tailored to serve as an autonomous subsystem providing authentication transparent for any application. Integration into a vehicle-to-vehicle communication system is shown as an application example.